2019
DOI: 10.30704/http-www-jivs-net.569912
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and paraclinical changes in experimental colisepticemia in neonatal calves

Abstract: The present study aim was to assess changes in clinical signs and plasma cytokines in calves experimentally infected with Escherchia coli and use them as a tool to diagnose colisepticemia. Ten healthy Holstein-Frisian bull calves were used for this experimental study. Experimental colisepticemia was induced in calves with intravenous injection of 1.5 × 109 CFU of O111:H8 strain of E.coli. Clinical scores were recorded before induction of septicemia, every 30 minutes for 8 hours, every hour from 8 till 12 h, ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…There has been some suggestion that vitamin C is effective Many studies have demonstrated the association between vitamin C and antibody levels in cattle. It has been reported that when the calves received colostrum are used orally 3 grams a day in the first week, 2 grams in the second week, and 1 gram in the third week, the amount of serum gamma globulin is increased significantly on the 14th day but not significantly on the 28th day (Lotfollahzadeh et al, 2005). In a study, vitamin C administered to calves was found to not affect the amount of total plasma IgG (Hidiroglou et al, 1995).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…There has been some suggestion that vitamin C is effective Many studies have demonstrated the association between vitamin C and antibody levels in cattle. It has been reported that when the calves received colostrum are used orally 3 grams a day in the first week, 2 grams in the second week, and 1 gram in the third week, the amount of serum gamma globulin is increased significantly on the 14th day but not significantly on the 28th day (Lotfollahzadeh et al, 2005). In a study, vitamin C administered to calves was found to not affect the amount of total plasma IgG (Hidiroglou et al, 1995).…”
Section: Discussionmentioning
confidence: 95%
“…The amount of IgG measured on days 14 and 28 in the vaccine-vitamin group was found to have increased significantly (P<0.05) compared to the vaccine group. It has been reported that vitamin C increases the amount of serum antibody in newborn calves (Lotfollahzadeh et al, 2005), calves vaccinated against Histophilus somni (Otomaru et al, 2021), in beef cattle vaccinated against Foot and Mouth disease (Kızıl & Gül, 2010), in dairy cattle with mastitis (Chaiyotwittayakun et al, 2002), in goats vaccinated with Brucella melitensis (İmik et al, 2000), chickens vaccinated against Newcastle virus (Gouda et al, 2020;Khan et al, 2014;Mirfendereski & Jahanian, 2015;Toplu et al, 2014), in chickens vaccinated against Infectious Bronchitis (Khan et al, 2014), in chickens vaccinated against Infectious Bursal Disease ( Wu et al, 2000), when injected into embryonated eggs (Zhu et al, 2019), in human lymphocytes in vitro (Tanaka et al, 1994), in mice vaccinated with Foot and Mount Disease (Wu et al, 2018). The results obtained in this study are consistent with the research results presented above.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation